Si vis Pacem, Cole Iustitiam. A Century of International Labour Organization - Gliksman, Adam (Warsaw Forum of Economic Sociology, 2019)
In 2019 the International Labour Organization celebrated its 100th anniversary. Established after the end of World War I, the organization aimed to improve working conditions and support actions for workers’ rights by negotiating labour standards through tripartite concertation involving representatives of employers, employees and governments, and by ensuring, through social justice, long-term global peace. Over the years, the ILO has developed methods of action allowing for achieving those goals by actively participating in solving the evolving problems of the world of work and labour. The article attempts to summarize the achievements of the ILO in the 1919–2019 period by analysing the directions of action and outlining the evolution of the activities of the organization.